Pelatihan Penerapan Teknologi Sauna UV untuk Pengeringan Rumput Laut yang Ramah Lingkungan - Wira Hadinata, Fitra; Rustanto, Dedi; Reza Supriadi, Abang; Hersal Armos, Nikanor; Tio, v; Gloria Apriliana Runtu, Kezia (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2025)
The number of seaweed farmers on Lemukutan Island is increasing, this is because people who were previously fishermen are also interested in this business. Seaweed cultivation businesses are divided into several types of activities, namely seaweed maintenance, seaweed drying, seaweed processing and selling processed seaweed. The time required for the seaweed drying process depends on the weather, because the drying process is under sunlight. This condition hampers seaweed sales and decreases the quality of the seaweed. A total of 15 participants who attended were able to understand the concept of UV sauna seaweed drying technology 90%, skills in the method of making UV sauna seaweed drying technology 80%.